Awareness regarding Coronary Heart Disease among Bachelor Level Students of a Selected College in Kathmandu - Gurung, Anju; Timilsina, Puja (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Coronary heart disease is characterized by an abnormal accumulation of lipid or fatty substances and fibrous tissue (called atheroma) that blocks and narrows the coronary arteries, depriving oxygen and reducing blood flow to the myocardium. The objective of this study was to find out the awareness regarding coronary heart disease among bachelor-level students of a selected college in Kathmandu, Nepal. Methods: A descriptive cross-sectional research design was used. The study was conducted in Tri-Chandra Multiple Campus, Ghantaghar, Kathmandu, Nepal. A total of 106 bachelor-level students were included. The data were collected using a self-administered semi-structured questionnaire. Descriptive and inferential statistics were used to analyse and interpret the findings. Results: Nearly half (47.2%) of the respondents had adequate level of awareness, 40.6% of the respondents had average level of awareness and only 12.2% of the respondents had inadequate level of awareness. There is no statistically significant association of level of awareness with age, sex, ethnicity, marital status and type of family regarding coronary heart disease among respondents. Conclusions: The students tend to have adequate awareness regarding coronary heart disease. Socio-demographic characteristics do not tend to influence the awareness regarding coronary heart disease among bachelor level students.